2010
DOI: 10.1007/s10457-010-9303-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of cocoa trees (Theobroma cacao) to a 13-month desiccation period in Sulawesi, Indonesia

Abstract: In South-east Asia, ENSO-related droughts represent irregularly occurring hazards for agroforestry systems containing cocoa which are predicted to increase in severity with expected climate warming. To characterize the drought response of mature cocoa trees, we conducted the Sulawesi Throughfall Displacement Experiment in a shaded (Gliricidia sepium) cocoa agroforestry system in Central Sulawesi, Indonesia. Three large sub-canopy roofs were installed to reduce throughfall by about 80% over a 13-month period to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 27 publications
3
76
0
9
Order By: Relevance
“…Other studies by Harteveld et al (2008) and Kummerow et al (1982) confirm that cacao fine roots extend well beyond the stem and are primarily concentrated in the uppermost 30 cm. Although overall autotrophic respiration rates appeared to decline, Moser et al (2010) reported that cacao and Gliricidia fine root biomass remained unchanged at all soil depths to 250 cm, over the duration of the 13-month induced drought. These findings suggest that regardless of the drought stress the trees still continued to maintain and build new fine roots required to search for available water resources.…”
Section: Drought Effects On Soil Co 2 Effluxmentioning
confidence: 94%
See 2 more Smart Citations
“…Other studies by Harteveld et al (2008) and Kummerow et al (1982) confirm that cacao fine roots extend well beyond the stem and are primarily concentrated in the uppermost 30 cm. Although overall autotrophic respiration rates appeared to decline, Moser et al (2010) reported that cacao and Gliricidia fine root biomass remained unchanged at all soil depths to 250 cm, over the duration of the 13-month induced drought. These findings suggest that regardless of the drought stress the trees still continued to maintain and build new fine roots required to search for available water resources.…”
Section: Drought Effects On Soil Co 2 Effluxmentioning
confidence: 94%
“…Additionally, a root excavation exercise done by Moser et al (2010) at the site, found that coarse roots of both cacao and Gliricidia were primarily concentrated around the tree stems while fine root (diameter<2 mm) distributions extended well into the agroforestry plantation. Other studies by Harteveld et al (2008) and Kummerow et al (1982) confirm that cacao fine roots extend well beyond the stem and are primarily concentrated in the uppermost 30 cm.…”
Section: Drought Effects On Soil Co 2 Effluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Low photosynthetic rates (A) and stomatal conductance (g s ) have been reported in cocoa trees with reductions due to water deficit, high vapor pressure deficit (VPD) and high photosynthetic photon flux density (PFD) among other abiotic factors that could cause stress (Deng et al 1989;de Almeida and Valle 2007;Acheampong et al 2013;Ávila-Lovera et al 2016). There are limited studies on ecophysiological responses to water and light availability of different genotypes of adult cocoa trees, both in agricultural ecosystems and natural habitats (Moser et al 2010;Araque et al 2012;Jaimez et al 2013;Ávila-Lovera et al 2016).…”
Section: Botanical Sciencesmentioning
confidence: 99%
“…Tanaman kakao dikategorikan sebagai tanaman yang sensitif terhadap kekeringan (Carr & Lockwood, 2011). Kondisi defisit air akan lebih berpengaruh negatif terhadap hasil biji daripada pertumbuhan kakao (Moser et al, 2010). Radiasi matahari dan temperatur tinggi serta perbedaan kelembapan (tekanan uap) di udara dan di daun selama periode kekeringan/defisit air, berdampak negatif terhadap asimilasi CO 2 di dalam proses metabolisme kakao.…”
Section: Pendahuluanunclassified